2015
DOI: 10.1080/0972060x.2014.998718
|View full text |Cite
|
Sign up to set email alerts
|

Anti-quorum Sensing Effetcs of Ethanolic Crude Extract ofAnethum graveolensL.

Abstract: In the recent years, effort to interfere with the quorum sensing (QS) has taken researchers consideration into the discovery and identification of bioactive compounds secreted by prokaryotes and eukaryotes. In this research, the anti-QS activity of thirty one plant species was detected through the inhibition of the QS related behaviors, violacein pigmentation in Chromobacterium violaceum CV026 and plant tissue maceration in Pectobacterium carotovorum. The results revealed that the arial parts extract of seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The results showed that the bacterial growth was not affected in the lower concentration treatment (6.25 mg/mL), and slightly affected in the medium concentration treatment (12.5 mg/mL), which was similar to the control (25 mg/mL 3,4 dibromo-2(5H)-furanone) ( Figure 8). The violacein inhibitory activity of HY026 and compound F1-4 observed in this study was higher than or similar to some other natural substances reported in similar research [20,21], such as eugenol [22] and malyngolide [23]. Besides the remarkable violacein inhibitory activity, F1-4 and actinomycin D standard could also inhibit prodigiosin production in Serratia proteamaculans 657 with the inhibition zone of 13.5 and 14 mm at 25 mg/disc.…”
Section: Bioactivity Of the Isolated Compoundsupporting
confidence: 73%
“…The results showed that the bacterial growth was not affected in the lower concentration treatment (6.25 mg/mL), and slightly affected in the medium concentration treatment (12.5 mg/mL), which was similar to the control (25 mg/mL 3,4 dibromo-2(5H)-furanone) ( Figure 8). The violacein inhibitory activity of HY026 and compound F1-4 observed in this study was higher than or similar to some other natural substances reported in similar research [20,21], such as eugenol [22] and malyngolide [23]. Besides the remarkable violacein inhibitory activity, F1-4 and actinomycin D standard could also inhibit prodigiosin production in Serratia proteamaculans 657 with the inhibition zone of 13.5 and 14 mm at 25 mg/disc.…”
Section: Bioactivity Of the Isolated Compoundsupporting
confidence: 73%
“…There are few studies reported that EOs based on QS inhibitory (QSI) property which have developed as food preservatives to enhance food safety, including Murraya koenigii , Cuminium cymium , and Myristica fragrans (nutmeg) (Bai & Vittal, 2014). In addition, EO components such as carvacrol and thymol could regulate the biofilm formation in Pseudomonas fluorescens KM121 and cyclohexasiloxane, eugenol and 1,2‐benzenedicarboxylic acid could inhibit the virulence in Pectobacterium carotovorum (Makhfian et al., 2015; Myszka et al., 2016). However, the mechanism of QSI effect of these EOs and its components has not been studied in depth.…”
Section: Introductionmentioning
confidence: 99%